Modeling language, cognition and action : (World Scientific, 2005)
This volume collects together peer reviewed versions of most of the papers presented at the Ninth Neural Computation and Psychology Workshop (NCPW9), held in 2004 at the University of Plymouth (England). The conference invited submissions on neural computation models of all cognitive and psychological processes. The special theme of this year's workshop was "Modeling of Language, Cognition and Action". This topic had the aim to extend the conference appeal from the connectionist psychology community to leaders in neuroscience, robotics and cognitive systems design. The chapters cover the breadth of research in neural computation and psychology, with numerous papers that focus on language modeling, this year's special theme. The book includes chapters from internationally renowned researchers in the various fields of cognitive psychology (such as Art Glenberg and Jonathan Evans) as well as computer science and robotics (such as Stefan Wermter & Stefano Nolfi).